Inter-Organelle NAD Metabolism Underpinning Light Responsive NADP Dynamics in Plants - Hashida, Shin-nosuke; Kawai-Yamada, Maki (Frontiers in Plant Science, 2019)
Upon illumination, photosystem I in chloroplasts catalyzes light-driven electron transport from plastocyanin to ferredoxin, followed by the reduction of NADP+ to NADPH by ferredoxin:NADP+ reductase for CO2 fixation. At the beginning of photosynthesis, NADP+ supply control is dominated by de novo NADP+ synthesis rather than being recycled from the Calvin cycle. Importantly, ferredoxin distributes electrons to NADP+ as well as to thioredoxins for light-dependent regulatory mechanisms, to cyclic electron flow for more ATP production, and to several metabolites for reductive reactions. We previously demonstrated that the NADP+ synthesis activity and the amount of the NADP pool size, namely the sum of NADP+ and NADPH, varies depending on the light conditions and the ferredoxin-thioredoxin system. In addition, the regulatory mechanism of cytoplasmic NAD+ supply is also involved in the chloroplastic NADP+ supply control because NAD+ is an essential precursor for NADP+ synthesis. In this mini-review, we summarize the most recent advances on our understanding of the regulatory mechanisms of NADP+ production, focusing on the interactions, crosstalk, and co-regulation between chloroplasts and the cytoplasm at the level of NAD+ metabolism and molecular transport.